2020
DOI: 10.3389/fnins.2020.00517
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Enhances Antidepressant/Antipsychotic Combination Therapy of Schizophrenia With Comorbid Depression in a Murine Model

Abstract: Comorbid depressive disorders confound the diagnosis and therapy of schizophrenia. Using a murine model incorporating both MK801 and chronic unpredictable mild stress exposures, we successfully replicated both psychosis and depression. Ex vivo patch clamp recordings and in vivo calcium imaging demonstrated impaired neural activity in the prefrontal cortex (PFC). We then administered triple-drug combinations consisting of two antidepressants (mirtazapine and venlafaxine) plus an antipsychotic (either clozapine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Through the analysis of reports of various types and the time of occurrence of DILI caused by different dosage forms of aripiprazole, we found that the time of occurrence in all cases was from 15 to 90 days (about 67.92% of the time) after continuous usage. This may be related to the fact that most of the clinical increases in the dose of this drug were done incrementally after 2 weeks of administration, and it may also be related to the length of the course of drug administration ( Zhou et al, 2020 ). In terms of recovery, 78.76% of patients improved or recovered after discontinuation of aripiprazole or suitable treatment, and this finding was consistent with the ease of recovery from the effects of aripiprazole on liver function that is reported in literature ( Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of reports of various types and the time of occurrence of DILI caused by different dosage forms of aripiprazole, we found that the time of occurrence in all cases was from 15 to 90 days (about 67.92% of the time) after continuous usage. This may be related to the fact that most of the clinical increases in the dose of this drug were done incrementally after 2 weeks of administration, and it may also be related to the length of the course of drug administration ( Zhou et al, 2020 ). In terms of recovery, 78.76% of patients improved or recovered after discontinuation of aripiprazole or suitable treatment, and this finding was consistent with the ease of recovery from the effects of aripiprazole on liver function that is reported in literature ( Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life and depressive symptomatology revealed no significant differences between the two study groups ( Supplementary Table 1 ). However, metformin showed antidepressant effects in larger cohorts and animal models ( 8 , 32 ), and was even shown to correct abnormal circadian rhythm on a cellular level via an activation of AMPK ( 33 ). Mechanistically, the action of metformin is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Data were compared using one-way analysis of variance and post hoc Tukey tests. Data analysis and figure plotting were performed with the GraphPad Prism software (version 8.0) [ 65 , 66 ]. No animals were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%